Prevalence of Cancer Types in Patients attending Mayo Hospital Lahore, Pakistan - Amjad, Sana; Saleem, Mehwish; Ashraf, Asfa; Iqbal, Muhammad Naeem (International Journal of Molecular Microbiology, 2020)
This study aimed to determine the prevalence of cancer types in patients attending Mayo Hospital Lahore, Pakistan. A retrospective study was conducted and the data was obtained from the medical record of the hospital for period of 2 years that is from 2016 to 2017. A predetermined scheme of analyzing individual files of patients attending the hospital for the study period was followed. All data were collected using standardized data collection Performa. Data were analyzed by using SPSS-20 and presented in the form of percentages and frequencies. During the study period, a total of 3610 patients were registered in the hospital. One thousand seven hundred and fifty-seven (48%) were male while one thousand eight hundred and fifty-three (52%) were female. The number of patients diagnosed throughout the study period was dominated in the year 2016 was 1820 (50.41%) patients. Eleven hundred and nineteen (31%) cases were from cancer of the genital system among them the carcinomas of breast were most prevalent 760 (21.05%). Digestive system tumors were 618 (17.11%) followed by oral cavity cancer 388 (10.73%). All the patients of oral cavity cancer were smokers or pan eaters or use some kind of drugs. Respiratory system tumors were 280 (7.75%). Head and Neck tumors recorded 214 (5.92%) cases. Blood cancer cases were 228 (6.31%) followed by Lymphoma 206 (5.7%) of total cases. Urinary system tumors were recorded in 161 (4.45%) cases. The cancer of different glands accounts for 84 (2.32%) of total cases. Primary unspecified region tumors highlighted 32 (0.88%) of the total cancer cases. Stages of only n=448 (12.4%) patients were mentioned out of n=3610 patients. The majority of the patients (70%) were reported at the 4th stage of cancer which is the most advanced stage of cancer and has very few chances of survival. The study concluded that the incidence rate of genital system tumors was highest among all cancer types during the study period. Further investigation should be done to find out the cause of cancer so that better prevention should be done.